Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ani12223105
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Content and Selected Quality Parameters of Sheep Milk Fermented Beverages during Storage

Abstract: The aim of the research was to evaluate lactose content and rheological, physical, chemical, and organoleptic parameters during the storage of fermented beverages made from sheep’s milk. The research was carried out on natural, probiotic, and Greek-type yogurts, as well as kefir. The products were made using the thermostat method from the milk of 42 East Frisian sheep in the middle lactation period, in duplicate. Lactose contents, active and titratable acidity, color by the L*a*b*C*h* system, and rheological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(33 reference statements)
3
2
0
Order By: Relevance
“…Thus, pH changed from around 6.70 in non-fermented milk to 3.80 after 48 h fermentation. Similar values have been previously reported for sheep milk kefir which had been fermented for the same time period [19,42,43], although the grains/milk ratio was not the same as in our work, i.e., 5% w/v. Lactic acid increased from an initial value of 0.056 g/L to 1.69 g/L after 48 h, similar to the results obtained by de Lima et al, 2018 [19], but lower than reported in a previous work [44], in which the authors measured around 9 g/L lactic acid.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, pH changed from around 6.70 in non-fermented milk to 3.80 after 48 h fermentation. Similar values have been previously reported for sheep milk kefir which had been fermented for the same time period [19,42,43], although the grains/milk ratio was not the same as in our work, i.e., 5% w/v. Lactic acid increased from an initial value of 0.056 g/L to 1.69 g/L after 48 h, similar to the results obtained by de Lima et al, 2018 [19], but lower than reported in a previous work [44], in which the authors measured around 9 g/L lactic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Actually, we did not observe a significant reduction in this metabolite, although its hydrolysis by-product D-galactose did clearly increase according to the fermentation time and with a very similar trend to that of lactic acid, indicating that there is a clear relationship between those compounds. The concentration values of lactose that we detected in our samples are quite similar to others already published, in the range of 30-50 g/L fermented product [42,[44][45][46]. Moreover, some studies have demonstrated that relatively low amounts of lactose disappear even after several days or weeks of storage after kefir production [42,45], thus indicating that during fermentation, lactose is not eliminated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The material for the study was fermented mare milk produced by the thermostat method under laboratory conditions [ 70 , 71 ]. The milk (9.4% dry matter content, pH 6.46, density 1.034 g/mL, 1.15% fat content) was purchased from a horse dairy farm in Kłodzin (Poland).…”
Section: Methodsmentioning
confidence: 99%
“…It is considered a source of functional bioactive peptides involved in processes related to the functioning of the digestive, endocrine, immune, and nervous systems [ 40 ]. Ovine milk products have therapeutic effects and are of great interest to consumers, especially people with limited lactose tolerance [ 41 ].…”
Section: Introductionmentioning
confidence: 99%